Patients' experiences of chronic non-malignant musculoskeletal pain: a qualitative systematic review. - Toye, F; Seers, K; Allcock, N; Briggs, M; Carr, E; Andrews, J; Barker, K (2013)
BACKGROUND: Musculoskeletal (MSK) pain is one of the most predominant types of pain and accounts for a large portion of the primary care workload. AIM: To systematically review and integrate the findings of qualitative research to increase understanding of patients' experiences of chronic non-malignant MSK pain. DESIGN AND SETTING: Synthesis of qualitative research using meta-ethnography using six electronic databases up until February 2012 (Medline, Embase, Cinahl, Psychinfo, Amed and HMIC). METHOD: Databases were searched from their inception until February 2012, supplemented by hand-searching contents lists of specific journals for 2001-2011 and citation tracking. Full published reports of qualitative studies exploring adults' own experience of chronic non-malignant MSK pain were eligible for inclusion. RESULTS: Out of 24 992 titles, 676 abstracts, and 321 full texts were screened, 77 papers reporting 60 individual studies were included. A new concept of pain as an adversarial struggle emerged. This adversarial struggle was to: 1) affirm self; 2) reconstruct self in time; 3) construct an explanation for suffering; 4) negotiate the healthcare system; and 5) prove legitimacy. However, despite this struggle there is also a sense for some patients of 6) moving forward alongside pain. CONCLUSIONS: This review provides a theoretical underpinning for improving patient experience and facilitating a therapeutic collaborative partnership. A conceptual model is presented, which offers opportunities for improvement by involving patients, showing them their pain is understood, and forming the basis to help patients move forward alongside their pain.